PENERAPAN TEORI BELAJAR HUMANISTIK DALAM PEMBELAJARAN - Perni, Ni Nyoman (Adi Widya: Jurnal Pendidikan Dasar, 2018)
Students are human beings whose human identity as a conscious subject needs to be defended and enforced through educational systems and models that are "free and egalitarian". The future challenge of education is to realize the process of learning democratization. A democratization process that reflects that learning is on children's initiative. To develop so that humans become mature, it is not enough if they are only trained, but also must be educated. Students must be educated for realists, recognize a life that is multidimensional, not uniform and invited to live a complementary diversity. Whereas in training, what is primarily formed is outward behavior. This learning theory talks more about the concepts of education to shape human beings who are aspired to, and about the learning process in its most ideal form. In other words, this theory is more interested in the notion of learning in its most ideal form than the understanding of the learning process as it is, as has been studied by other learning theories. In its implementation, this humanistic theory, among others, also appears in the learning approach proposed by Ausubel.